2016
DOI: 10.3389/fphys.2016.00269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prior Intense Exercise and Cold Water Immersion in Recovery for Performance and Physiological Response during Subsequent Exercise

Abstract: Athletes in intense endurance sports (e.g., 4000-m track cycling) often perform maximally (~4 min) twice a day due to qualifying and finals being placed on the same day. The purpose of the present study was to evaluate repeated performance on the same day in a competitive setting (part A) and the influence from prior intense exercise on subsequent performance and physiological response to moderate and maximal exercise with and without the use of cold water immersion (CWI) in recovery (part B). In part A, perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Yet although CWI has a positive effect on recovery (Versey et al 2013), the effect of immersion between two successive exercise bouts has not been studied much. Recently, Christensen and Bangsbo (2016) showed that CWI recovery (15 min at 15°C) did not lead to better subsequent performance in a simulated competition (two maximal ~4-min efforts separated by 3 hr). Vaile et al (2008) showed that three water immersion conditions (10°C, 15°C, 20°C) were effective in reducing thermal strain and more effective than active recovery in maintaining subsequent highintensity cycling performance.…”
Section: Résumémentioning
confidence: 99%
“…Yet although CWI has a positive effect on recovery (Versey et al 2013), the effect of immersion between two successive exercise bouts has not been studied much. Recently, Christensen and Bangsbo (2016) showed that CWI recovery (15 min at 15°C) did not lead to better subsequent performance in a simulated competition (two maximal ~4-min efforts separated by 3 hr). Vaile et al (2008) showed that three water immersion conditions (10°C, 15°C, 20°C) were effective in reducing thermal strain and more effective than active recovery in maintaining subsequent highintensity cycling performance.…”
Section: Résumémentioning
confidence: 99%
“…Submersion into cold water (Յ15°C) after training and competition has become a routine for many athletes, such as those engaged in cycling and football. Cold-water immersion (CWI) in recovery has been shown to reduce the decline in maximal force (8) and intense exercise performance (40) invoked by prior intense exercise, although effects of CWI were absent (10,61) or even detrimental to physical recovery (9) in other studies. While the impact of CWI in recovery on subsequent physical performance is well studied, few studies have examined its effects on training adaptation.…”
Section: Introductionmentioning
confidence: 99%